Indomilk and Chitato's Strategy to Make Seventeen Their Brand Ambassador to Reach the Indonesian Market - Agnes Tamara Winda; Erwin Permana; Lazarus Sinaga (Managing: Jurnal Bisnis dan Manajemen, 2026)
The food and beverage industry in Indonesia is increasingly competitive, prompting companies to adopt innovative marketing strategies. One strategy that is increasingly popular is the use of brand ambassadors from global celebrities, including K-pop idols. This study discusses Indomilk Chitato's marketing strategy in collaborating with SEVENTEEN as their brand ambassadors. Using a qualitative descriptive approach through digital tracking and observation, the results of the study show that this collaboration has succeeded in increasing consumer appeal and engagement, especially among K-pop fans in Indonesia.Indomilk and Chitato selected three members of SEVENTEEN—S.Coups, Wonwoo, and Vernon—to build emotional connections with the target market through interactive digital campaigns, special edition packaging, and exclusive merchandise. The use of celebrity endorsements and the use of fandom culture have proven effective in increasing brand awareness, creating unique experiences for consumers, and strengthening the product's position in the market. This strategy was reinforced with digital campaigns on Instagram, Twitter, and TikTok, where consumer interaction was driven through online challenges and giveaways. In addition, the “Wave Here on 17 Dec” event provided an opportunity for fans to interact directly with their idols, strengthening the emotional connection between the brand and its consumers. This experience-based marketing increases customer loyalty and attracts wider public attention.